Q500 yield strength grade weather-proof bridge steel welding rod and preparation method thereof
By preparing to prepare the weather -resistant steel electrodes prepared by the pink ratio of potassium and sodium water glass in the bridge steel structure, the welding material has been solved the challenge of low temperature and crispness and wind resistance performance at the Q500 yield strength level, and the high yield strength and excellent low temperature are achieved. Toughness of toughness.
Patent Information
- Application Number
- CN202411785193.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-01-24
AI Technical Summary
In bridge steel structures, the low-temperature brittleness and wind resistance of welding materials are challenging, especially in the application of Q500 yield strength grade weathering steel, which is difficult to take into account high yield strength and excellent low-temperature toughness.
A weathering steel electrode with high and low temperature toughness is prepared by adding potash-sodium water glass to a specific ratio of powder mixture, pressure-coating it on the carbon steel core and then drying it. The powder ratio of the welding rod includes marble, fluorite, rutile, feldspar, lithium fluoride, ferrosilicon, electrolytic manganese, nickel powder, metal chromium, iron powder, silicon-zirconium alloy, copper powder, cerium oxide, yttrium oxide, Ingredients such as sodium alginate and soda ash.
While satisfying the Q500 yield strength level, this stripe shows excellent -40 ℃ low temperature toughness, and has high-electric arcs, stable burning, less splashing, good molding and excellent mechanical performance during the welding process.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention relates to the field of welding materials, in particular to a welding rod for Q500 yield strength grade weathering steel and a preparation method thereof. Background Art
[0002] Bridges are an important part of modern basic transportation facilities and are the weak and key nodes of modern traffic arteries. The safety and reliability of bridges are directly related to the safety of people's lives and property as well as social and economic development. In the process of bridge construction, welding technology is widely used in the connection of steel structures, and the performance of welding materials plays a vital role in the quality and performance of welded joints.
[0003] Weathering bridge steel is made by adding alloy elements such as Cu, Cr, and Ni to ordinary bridge steel to improve corrosion resistance. A certain amount of Cu, Cr, Ni and other elements also need to be added to the welding materials when designing the composition to improve the atmospheric corrosion resistance of the weld. However, the increase of these elements may increase the toughness-brittleness transition temperature of the weld, making the low-temperature brittleness of the weld worse. Furthermore, the application environment of weathering bridge steel is more complex, and a strong arc stiffness is required to improve wind resistance. At the same time, the yield strength requirements of weathering steel are relatively high (≥500Mpa), and there are also problems with the comprehensive matching of the strength and plasticity, low-temperature toughness, and weldability of the bridge steel plate. Summary of the invention
[0004] The object of the present invention is to provide a Q500 yield strength grade weathering steel welding rod. The present invention has surprisingly found that the welding rod having the characteristics of the present invention exhibits excellent -40°C low temperature toughness while meeting the Q500 yield strength grade. The present invention has been completed by this discovery.
[0005] To this end, the first aspect of the present invention provides a weathering steel welding rod with high and low temperature toughness, characterized in that it is made by mixing the following powders in weight proportions, then adding 22-27% of potassium sodium water glass accounting for the total weight of the mixed powders, stirring evenly, pressing and coating on a carbon steel welding core (e.g., a H08A welding core of Φ2-6mm) and then drying (e.g., drying at low temperature for 12 hours and then drying at high temperature); the weight proportion of the powders is: 20-25 parts of marble, 17-22 parts of fluorite, 2-5 parts of rutile, 3-8 parts of feldspar, 4-7 parts of lithium fluoride, 3-5 parts of ferrosilicon, 6-10 parts of electrolytic manganese, 2-4 parts of nickel powder, 1.5-3.5 parts of metallic chromium, 7-10 parts of iron powder, 2-4 parts of silicon-zirconium alloy, 2.5-3.5 parts of copper powder, 1.0-1.5 parts of cerium oxide, 0.5-0.8 parts of yttrium oxide, 1-3 parts of sodium alginate, and 1-2 parts of soda ash.
[0006] The high and low temperature toughness weathering steel welding rod according to any embodiment of the first aspect of the present invention is characterized in that the specification of the welding core is Φ2.5~5.0mm.
[0007] The high and low temperature toughness weathering steel welding rod according to any embodiment of the first aspect of the present invention is characterized in that the specification of the welding core is Ф2.5mm, Ф3.2mm, Ф4.0mm or Ф5.0mm.
[0008] The high and low temperature toughness weathering steel welding rod according to any embodiment of the first aspect of the present invention is characterized in that the weight ratio of the powder is (e1): 20 parts of marble, 21 parts of fluorite, 3 parts of rutile, 5 parts of feldspar, 6 parts of lithium fluoride, 3 parts of ferrosilicon, 8 parts of electrolytic manganese, 2 parts of nickel powder, 2 parts of metallic chromium, 7 parts of iron powder, 2 parts of silicon zirconium alloy, 3.5 parts of copper powder, 1 part of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 1 part of soda ash.
[0009] The high and low temperature toughness weathering steel welding rod according to any embodiment of the first aspect of the present invention is characterized in that the weight ratio of the powder is (e2): 22 parts of marble, 18 parts of fluorite, 2 parts of rutile, 3 parts of feldspar, 5 parts of lithium fluoride, 4 parts of ferrosilicon, 7 parts of electrolytic manganese, 3 parts of nickel powder, 1.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.4 parts of cerium oxide, 0.7 parts of yttrium oxide, 2 parts of sodium alginate, and 1.5 parts of soda ash.
[0010] The high and low temperature toughness weathering steel welding rod according to any embodiment of the first aspect of the present invention is characterized in that the weight ratio of the powder is (e3): 23 parts of marble, 22 parts of fluorite, 4 parts of rutile, 8 parts of feldspar, 7 parts of lithium fluoride, 5 parts of ferrosilicon, 6 parts of electrolytic manganese, 4 parts of nickel powder, 3.5 parts of metallic chromium, 8 parts of iron powder, 4 parts of silicon zirconium alloy, 2.5 parts of copper powder, 1.3 parts of cerium oxide, 0.6 parts of yttrium oxide, 2 parts of sodium alginate, and 2 parts of soda ash.
[0011] The high and low temperature toughness weathering steel welding rod according to any embodiment of the first aspect of the present invention is characterized in that the weight ratio of the powder is (e4): 24 parts of marble, 19 parts of fluorite, 5 parts of rutile, 7 parts of feldspar, 4 parts of lithium fluoride, 3 parts of ferrosilicon, 9 parts of electrolytic manganese, 2 parts of nickel powder, 2.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.2 parts of cerium oxide, 0.5 parts of yttrium oxide, 1 part of sodium alginate, and 1.5 parts of soda ash.
[0012] The high and low temperature toughness weathering steel welding rod according to any embodiment of the first aspect of the present invention is characterized in that the weight ratio of the powder is (e5): 25 parts of marble, 17 parts of fluorite, 3 parts of rutile, 6 parts of feldspar, 5 parts of lithium fluoride, 5 parts of ferrosilicon, 10 parts of electrolytic manganese, 4 parts of nickel powder, 3 parts of metallic chromium, 10 parts of iron powder, 2 parts of silicon zirconium alloy, 2.5 parts of copper powder, 1.5 parts of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 2 parts of soda ash.
[0013] According to any embodiment of the first aspect of the present invention, the high and low temperature toughness weathering steel welding rod is characterized in that the weight ratio of the powder is (e1): 20 parts of marble, 21 parts of fluorite, 3 parts of rutile, 5 parts of feldspar, 6 parts of lithium fluoride, 3 parts of ferrosilicon, 8 parts of electrolytic manganese, 2 parts of nickel powder, 2 parts of metallic chromium, 7 parts of iron powder, 2 parts of silicon zirconium alloy, 3.5 parts of copper powder, 1 part of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 1 part of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 27 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ4.0 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0014] According to any embodiment of the first aspect of the present invention, the weathering steel welding rod with high and low temperature toughness is characterized in that the weight ratio of the powder is (e2): 22 parts of marble, 18 parts of fluorite, 2 parts of rutile, 3 parts of feldspar, 5 parts of lithium fluoride, 4 parts of ferrosilicon, 7 parts of electrolytic manganese, 3 parts of nickel powder, 1.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.4 parts of cerium oxide, 0.7 parts of yttrium oxide, 2 parts of sodium alginate, and 1.5 parts of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 24 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ2.5 mm welding core (H08A) by a hydraulic press, and drying the welding rod at a low temperature (45° C.) for 12 hours, and then drying at a high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0015] According to any embodiment of the first aspect of the present invention, the weathering steel welding rod with high and low temperature toughness is characterized in that the weight ratio of the powder is (e3): 23 parts of marble, 22 parts of fluorite, 4 parts of rutile, 8 parts of feldspar, 7 parts of lithium fluoride, 5 parts of ferrosilicon, 6 parts of electrolytic manganese, 4 parts of nickel powder, 3.5 parts of metallic chromium, 8 parts of iron powder, 4 parts of silicon-zirconium alloy, 2.5 parts of copper powder, 1.3 parts of cerium oxide, 0.6 parts of yttrium oxide, 2 parts of sodium alginate, and 2 parts of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 26 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ3.2 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0016] According to any embodiment of the first aspect of the present invention, the weathering steel welding rod with high and low temperature toughness is characterized in that the weight ratio of the powder is (e4): 24 parts of marble, 19 parts of fluorite, 5 parts of rutile, 7 parts of feldspar, 4 parts of lithium fluoride, 3 parts of ferrosilicon, 9 parts of electrolytic manganese, 2 parts of nickel powder, 2.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.2 parts of cerium oxide, 0.5 parts of yttrium oxide, 1 part of sodium alginate, and 1.5 parts of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 23 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ4.0 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0017] According to any embodiment of the first aspect of the present invention, the high and low temperature toughness weathering steel welding rod is characterized in that the weight ratio of the powder is (e5): 25 parts of marble, 17 parts of fluorite, 3 parts of rutile, 6 parts of feldspar, 5 parts of lithium fluoride, 5 parts of ferrosilicon, 10 parts of electrolytic manganese, 4 parts of nickel powder, 3 parts of metallic chromium, 10 parts of iron powder, 2 parts of silicon zirconium alloy, 2.5 parts of copper powder, 1.5 parts of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 2 parts of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 22 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ5.0 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0018] Furthermore, the second aspect of the present invention provides a method for preparing a weathering steel welding rod, which comprises the following steps: (a) mixing the following powders in weight proportions uniformly: 20-25 parts of marble, 17-22 parts of fluorite, 2-5 parts of rutile, 3-8 parts of feldspar, 4-7 parts of lithium fluoride, 3-5 parts of ferrosilicon, 6-10 parts of electrolytic manganese, 2-4 parts of nickel powder, 1.5-3.5 parts of metallic chromium, 7-10 parts of iron powder, 2-4 parts of silicon-zirconium alloy, 2.5-3.5 parts of copper powder, 1.0-1.5 parts of cerium oxide, 0.5-0.8 parts of yttrium oxide, 1-3 parts of sodium alginate, and 1-2 parts of soda ash; (b) adding 22 to 27 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder of step (a), stirring evenly, applying the mixture to a carbon steel welding core (e.g., a H08A welding core of Φ2 to 6 mm), and then drying (e.g., drying at low temperature for 12 hours and then drying at high temperature, e.g., drying at low temperature (45°C) for 12 hours and then drying at high temperature (360°C) for 2 hours) to obtain a weathering steel welding rod.
[0019] The method according to any embodiment of the second aspect of the present invention is characterized in that the specification of the welding core is Φ2.5~5.0mm.
[0020] The method according to any embodiment of the second aspect of the present invention is characterized in that the specification of the welding core is Ф2.5mm, Ф3.2mm, Ф4.0mm or Ф5.0mm.
[0021] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e1): 20 parts of marble, 21 parts of fluorite, 3 parts of rutile, 5 parts of feldspar, 6 parts of lithium fluoride, 3 parts of ferrosilicon, 8 parts of electrolytic manganese, 2 parts of nickel powder, 2 parts of metallic chromium, 7 parts of iron powder, 2 parts of silicon zirconium alloy, 3.5 parts of copper powder, 1 part of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 1 part of soda ash.
[0022] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e2): 22 parts of marble, 18 parts of fluorite, 2 parts of rutile, 3 parts of feldspar, 5 parts of lithium fluoride, 4 parts of ferrosilicon, 7 parts of electrolytic manganese, 3 parts of nickel powder, 1.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.4 parts of cerium oxide, 0.7 parts of yttrium oxide, 2 parts of sodium alginate, and 1.5 parts of soda ash.
[0023] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e3): 23 parts of marble, 22 parts of fluorite, 4 parts of rutile, 8 parts of feldspar, 7 parts of lithium fluoride, 5 parts of ferrosilicon, 6 parts of electrolytic manganese, 4 parts of nickel powder, 3.5 parts of metallic chromium, 8 parts of iron powder, 4 parts of silicon zirconium alloy, 2.5 parts of copper powder, 1.3 parts of cerium oxide, 0.6 parts of yttrium oxide, 2 parts of sodium alginate, and 2 parts of soda ash.
[0024] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e4): 24 parts of marble, 19 parts of fluorite, 5 parts of rutile, 7 parts of feldspar, 4 parts of lithium fluoride, 3 parts of ferrosilicon, 9 parts of electrolytic manganese, 2 parts of nickel powder, 2.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.2 parts of cerium oxide, 0.5 parts of yttrium oxide, 1 part of sodium alginate, and 1.5 parts of soda ash.
[0025] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e5): 25 parts of marble, 17 parts of fluorite, 3 parts of rutile, 6 parts of feldspar, 5 parts of lithium fluoride, 5 parts of ferrosilicon, 10 parts of electrolytic manganese, 4 parts of nickel powder, 3 parts of metallic chromium, 10 parts of iron powder, 2 parts of silicon zirconium alloy, 2.5 parts of copper powder, 1.5 parts of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 2 parts of soda ash.
[0026] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e1): 20 parts of marble, 21 parts of fluorite, 3 parts of rutile, 5 parts of feldspar, 6 parts of lithium fluoride, 3 parts of ferrosilicon, 8 parts of electrolytic manganese, 2 parts of nickel powder, 2 parts of metallic chromium, 7 parts of iron powder, 2 parts of silicon zirconium alloy, 3.5 parts of copper powder, 1 part of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 1 part of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 27 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ4.0 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0027] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e2): 22 parts of marble, 18 parts of fluorite, 2 parts of rutile, 3 parts of feldspar, 5 parts of lithium fluoride, 4 parts of ferrosilicon, 7 parts of electrolytic manganese, 3 parts of nickel powder, 1.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.4 parts of cerium oxide, 0.7 parts of yttrium oxide, 2 parts of sodium alginate, and 1.5 parts of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 24 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ2.5 mm welding core (H08A) by a hydraulic press, and drying the welding rod at a low temperature (45° C.) for 12 hours, and then drying at a high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0028] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e3): 23 parts of marble, 22 parts of fluorite, 4 parts of rutile, 8 parts of feldspar, 7 parts of lithium fluoride, 5 parts of ferrosilicon, 6 parts of electrolytic manganese, 4 parts of nickel powder, 3.5 parts of metallic chromium, 8 parts of iron powder, 4 parts of silicon zirconium alloy, 2.5 parts of copper powder, 1.3 parts of cerium oxide, 0.6 parts of yttrium oxide, 2 parts of sodium alginate, and 2 parts of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 26 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ3.2 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0029] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e4): 24 parts of marble, 19 parts of fluorite, 5 parts of rutile, 7 parts of feldspar, 4 parts of lithium fluoride, 3 parts of ferrosilicon, 9 parts of electrolytic manganese, 2 parts of nickel powder, 2.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.2 parts of cerium oxide, 0.5 parts of yttrium oxide, 1 part of sodium alginate, and 1.5 parts of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 23 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ4.0 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0030] The method according to any embodiment of the second aspect of the present invention is characterized in that the weight ratio of the powder is (e5): 25 parts of marble, 17 parts of fluorite, 3 parts of rutile, 6 parts of feldspar, 5 parts of lithium fluoride, 5 parts of ferrosilicon, 10 parts of electrolytic manganese, 4 parts of nickel powder, 3 parts of metallic chromium, 10 parts of iron powder, 2 parts of silicon-zirconium alloy, 2.5 parts of copper powder, 1.5 parts of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 2 parts of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 22 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ5.0 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
[0031] In the powder material ratio of the present invention, due to strict control of raw materials and reasonable alloy ratio, the welding rod has high arc stiffness, less spatter, complete slag coverage, good slag removal, good operability during welding, smooth weld formation, and the deposited metal has excellent high mechanical properties.
[0032] In the steps of the above-mentioned preparation method of the present invention, although the specific steps described therein are different from the steps described in the preparation examples in the specific implementation mode part below in some details or language descriptions, those skilled in the art can fully summarize the above-mentioned method steps based on the detailed disclosure of the full text of the present invention.
[0033] Any embodiment of the present invention can be combined with other embodiments, as long as they do not conflict. In addition, in any embodiment of the present invention, any technical feature can be applied to the technical features in other embodiments, as long as they do not conflict. The present invention is further described below.
[0034] The various terms and phrases used in the present invention have general meanings known to those skilled in the art. Even so, the present invention still hopes to provide a more detailed description and explanation of these terms and phrases herein. If the mentioned terms and phrases are inconsistent with the known meanings, the meanings expressed in the present invention shall prevail.
[0035] In the present invention, the term "parts by weight" indicates the relative amount of each component in the electrode coating of the present invention, and the "parts by weight" may be an absolute weight (e.g., mg, g, or kg, etc.) or a weight percentage (e.g., weight % or wt%). Of course, when expressed in weight percentage (e.g., weight % or wt%), a preferred embodiment is that the sum of each component is 100%.
[0036] In the present invention, the various ingredients used are well known in the art, such as marble, fluorite, rutile, sodium alginate, ferrotitanium, electrolytic manganese, metallic chromium, iron powder, silicon-zirconium alloy, copper powder, cerium oxide, yttrium oxide, potassium-sodium water glass and the like, which can be directly purchased from the market under the above-mentioned product names.
[0037] In order to facilitate understanding of the invention, the main functions of the various components of the Chinese medicinal skin raw material of the present invention are described as follows.
[0038] Marble, fluorite and lithium fluoride are added to the coating as gasifiers and slag-forming agents, which can strengthen the arc, protect the welding pool and improve the weld formation. Marble decomposes into CaO and CO2 under the action of arc heat, slag and gasification, which can increase the basicity of slag, stabilize the arc, refine the molten droplets, increase the interfacial tension between slag and metal, improve slag removal, and have good desulfurization ability; fluorite and lithium fluoride can slag, protect the welding pool and improve the weld formation, and have a dehydrogenation effect.
[0039] Rutile is added to the coating as an arc stabilizer, making it easier for the electrode to strike an arc and keep the arc burning stably during the welding process. At the same time, it adjusts the melting point, viscosity, surface tension and fluidity of the slag, improves weld formation and reduces spatter.
[0040] Sodium alginate and soda ash are added to the coating as pressure-coating lubricants, mainly to improve the pressure-coating properties of the welding rod.
[0041] Atomized ferrosilicon, electrolytic manganese, and silicon-zirconium alloy are added to the coating as deoxidizers and desulfurizers. Through metallurgical reactions during welding, the oxygen content in the weld metal is reduced, the properties of the weld metal are improved, and the toughness of the weld metal is improved.
[0042] Metal chromium, nickel powder and copper powder are added to the coating as alloying agents to pass alloy elements into the weld and improve the weld strength and weather resistance.
[0043] Cerium oxide and yttrium oxide can refine the grains and improve low-temperature impact toughness.
[0044] According to any embodiment of the present invention, the welding core used to prepare the welding rod is a typical welding wire.
[0045] A weathering steel welding rod with high and low temperature toughness according to the present invention has the following significant advantages: 1. The arc is high in stiffness, the combustion is stable and there is little spatter during welding.
[0046] 2. During welding, the operability is good, the weld slag is completely covered, the weld is well formed, and the slag is easy to remove.
[0047] 3. When the yield strength of the weld metal is guaranteed to be ≥500Mpa, it has excellent low-temperature toughness, and the Charpy impact absorption energy at -40℃ is still ≥100J.
[0048] 4. The weld metal has a low diffusible hydrogen content, and the diffusible hydrogen measured by the mercury method is ≤3.0ml / 100g.
[0049] Generally speaking, the flux prepared by the present invention exhibits excellent effects in one or more aspects. DETAILED DESCRIPTION
[0050] The present invention can be further described by the following examples, however, the scope of the present invention is not limited to the following examples. It will be appreciated by those skilled in the art that various changes and modifications may be made to the present invention without departing from the spirit and scope of the present invention. The present invention provides general and / or specific descriptions of the materials and test methods used in the test. Although many materials and operating methods used to achieve the purpose of the present invention are well known in the art, the present invention is still described in as much detail as possible at this point.
[0051] Example 1: Preparation of Q500 yield strength weathering bridge steel welding rod (a) taking 20 parts of marble, 21 parts of fluorite, 3 parts of rutile, 5 parts of feldspar, 6 parts of lithium fluoride, 3 parts of ferrosilicon, 8 parts of electrolytic manganese, 2 parts of nickel powder, 2 parts of metallic chromium, 7 parts of iron powder, 2 parts of silicon zirconium alloy, 3.5 parts of copper powder, 1 part of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 1 part of soda ash, and mixing the powders of the materials uniformly; (b) For every 100 parts by weight of the mixed powder of step (a), 27 parts by weight of potassium sodium water glass are added to the dry powder and mixed evenly, and then applied to a Φ4.0 mm welding core (H08A, unless otherwise specified, the present invention uses the H08A type welding core) by a hydraulic press. The welding rod is dried at low temperature (45°C) for 12 hours and then dried at high temperature (360°C) for 2 hours to obtain a Q500 yield strength grade weather-resistant bridge steel welding rod, which is denoted as J557NHQ.
[0052] The Q500 yield strength weathering bridge steel welding rod J557NHQ obtained in this embodiment is used to weld the carbon steel plate base material (Q345NH hot-rolled weathering angle steel, specification ∠200mm×200mm×20mm), with a welding current of 160~180A, an arc voltage of 24V, and a welding speed of 15cm / min. Its welding process performance is excellent, for example: the arc stiffness is high, stable, and spatter is small during welding, the weld slag is completely covered, the slag is well removed, the weld is smooth and excellent, and the weld metal has excellent mechanical properties and low diffusible hydrogen content. The welding process record of this embodiment is shown in Table 1, and the mechanical properties and diffusible hydrogen content of the weld metal are shown in Table 2.
[0053] Example 2: Preparation of Q500 yield strength weathering bridge steel welding rod (a) taking 22 parts of marble, 18 parts of fluorite, 2 parts of rutile, 3 parts of feldspar, 5 parts of lithium fluoride, 4 parts of ferrosilicon, 7 parts of electrolytic manganese, 3 parts of nickel powder, 1.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.4 parts of cerium oxide, 0.7 parts of yttrium oxide, 2 parts of sodium alginate, and 1.5 parts of soda ash in parts by weight, and mixing the powders of the materials uniformly; (b) For every 100 parts by weight of the mixed powder of step (a), 24 parts by weight of potassium sodium water glass are added to the dry powder and mixed evenly, and then applied to a Φ2.5 mm welding core (H08A) by a hydraulic press. The welding rod is dried at a low temperature (45°C) for 12 hours and then dried at a high temperature (360°C) for 2 hours to obtain a Q500 yield strength grade weather-resistant bridge steel welding rod, which is denoted as J557NHQ.
[0054] The Q500 yield strength weathering bridge steel welding rod J557NHQ obtained in this embodiment is used to weld the carbon steel plate base material (Q345NH hot-rolled weathering angle steel, specification ∠200mm×200mm×20mm), and the welding current is 60~90A. Its welding process performance is excellent, for example: the arc stiffness is high, stable, and there is less spatter during welding, the weld slag is completely covered, the slag is well removed, the weld is smooth and excellent, and the weld metal has excellent mechanical properties and low diffusible hydrogen content. The welding process record of this embodiment is shown in Table 1, and the mechanical properties and diffusible hydrogen content of the weld metal are shown in Table 2.
[0055] Example 3: Preparation of Q500 yield strength weathering bridge steel welding rod (a) taking 23 parts of marble, 22 parts of fluorite, 4 parts of rutile, 8 parts of feldspar, 7 parts of lithium fluoride, 5 parts of ferrosilicon, 6 parts of electrolytic manganese, 4 parts of nickel powder, 3.5 parts of metallic chromium, 8 parts of iron powder, 4 parts of silicon-zirconium alloy, 2.5 parts of copper powder, 1.3 parts of cerium oxide, 0.6 parts of yttrium oxide, 2 parts of sodium alginate, and 2 parts of soda ash, and mixing the powders of the materials uniformly; (b) For every 100 parts by weight of the mixed powder of step (a), 26 parts by weight of potassium sodium water glass are added to the dry powder and mixed evenly, and then applied to a Φ3.2 mm welding core (H08A) by a hydraulic press. The welding rod is dried at a low temperature (45°C) for 12 hours and then dried at a high temperature (360°C) for 2 hours to obtain a Q500 yield strength grade weather-resistant bridge steel welding rod, which is denoted as J557NHQ.
[0056] The Q500 yield strength weathering bridge steel welding rod J557NHQ obtained in this embodiment is used to weld the carbon steel plate base material (Q345NH hot-rolled weathering angle steel, specification ∠200mm×200mm×20mm), with a welding current of 160~180A, an arc voltage of 24V, and a welding speed of 15cm / min. Its welding process performance is excellent, for example: the arc stiffness is high, stable, and spatter is small during welding, the weld slag is completely covered, the slag is well removed, the weld is smooth and excellent, and the weld metal has excellent mechanical properties and low diffusible hydrogen content. The welding process record of this embodiment is shown in Table 1, and the mechanical properties and diffusible hydrogen content of the weld metal are shown in Table 2.
[0057] Example 4: Preparation of a Q500 yield strength weathering bridge steel welding rod (a) taking 24 parts of marble, 19 parts of fluorite, 5 parts of rutile, 7 parts of feldspar, 4 parts of lithium fluoride, 3 parts of ferrosilicon, 9 parts of electrolytic manganese, 2 parts of nickel powder, 2.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.2 parts of cerium oxide, 0.5 parts of yttrium oxide, 1 part of sodium alginate, and 1.5 parts of soda ash, and mixing the powders of the materials uniformly; (b) For every 100 parts by weight of the mixed powder of step (a), 23 parts by weight of potassium sodium water glass are added to the dry powder and mixed evenly, and then applied to a Φ4.0 mm welding core (H08A) by a hydraulic press. The welding rod is dried at a low temperature (45° C.) for 12 hours and then dried at a high temperature (360° C.) for 2 hours to obtain a Q500 yield strength grade weather-resistant bridge steel welding rod, which is designated as J557NHQ.
[0058] The Q500 yield strength weathering bridge steel welding rod J557NHQ obtained in this embodiment is used to weld the carbon steel plate base material (Q345NH hot-rolled weathering angle steel, specification ∠200mm×200mm×20mm), with a welding current of 160~180A, an arc voltage of 24V, and a welding speed of 15cm / min. Its welding process performance is excellent, for example: the arc stiffness is high, stable, and spatter is small during welding, the weld slag is completely covered, the slag is well removed, the weld is smooth and excellent, and the weld metal has excellent mechanical properties and low diffusible hydrogen content. The welding process record of this embodiment is shown in Table 1, and the mechanical properties and diffusible hydrogen content of the weld metal are shown in Table 2.
[0059] Example 5: Preparation of a Q500 yield strength weathering bridge steel welding rod (a) taking, by weight, 25 parts of marble, 17 parts of fluorite, 3 parts of rutile, 6 parts of feldspar, 5 parts of lithium fluoride, 5 parts of ferrosilicon, 10 parts of electrolytic manganese, 4 parts of nickel powder, 3 parts of metallic chromium, 10 parts of iron powder, 2 parts of silicon-zirconium alloy, 2.5 parts of copper powder, 1.5 parts of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 2 parts of soda ash, and mixing the powders of the materials uniformly; (b) For every 100 parts by weight of the mixed powder of step (a), 22 parts by weight of potassium sodium water glass are added to the dry powder and mixed evenly, and then applied to a Φ5.0 mm welding core (H08A) by a hydraulic press. The welding rod is dried at a low temperature (45°C) for 12 hours and then dried at a high temperature (360°C) for 2 hours to obtain a Q500 yield strength grade weather-resistant bridge steel welding rod, which is denoted as J557NHQ.
[0060] The Q500 yield strength grade weathering bridge steel welding rod J557NHQ obtained in this embodiment is used to weld the carbon steel plate base material (Q345NH hot-rolled weathering steel, specification (300mm×150mm×20mm), the welding current is 160~180A, the arc voltage is 24V, and the welding speed is 15cm / min. Its welding process performance is excellent, for example: the arc stiffness is high, stable, and there is less spatter during welding, the weld slag is completely covered, the slag is well removed, the weld is smooth and excellent, and the weld metal has excellent mechanical properties and low diffusible hydrogen content. The welding process record of this embodiment is shown in Table 1, and the mechanical properties and diffusible hydrogen content of the weld metal are shown in Table 2.
[0061] Table 1: Welding processability record
[0062] 2: Mechanical properties of weld metal and diffusible hydrogen content
[0063] The test methods for the mechanical properties of the deposited metals, such as the tensile strength, yield strength and elongation after room temperature stretching in the table, refer to GB / T228.1-2010 (Tensile test of metallic materials Part 1 - Room temperature test method [S], the result is the average of n=5), the -40℃ impact energy test method refers to GB / T229-2020 Charpy pendulum impact test method for metallic materials [S]), and the test method for the diffusible hydrogen content is carried out in accordance with GB / T3965-2012.
[0064] It is well known that when the tensile strength and yield strength are at appropriate values, the higher the elongation after fracture, the higher the impact energy, and the lower the diffusible hydrogen, the better the performance of the welding rod. Although the materials used in Examples 1 to 5 are the same and the composition ratios of each component are within the relevant range, it is unexpectedly found that the irregular composition ratios of these five embodiments show significant differences in elongation after fracture, -40℃ impact energy, and mercury diffusible hydrogen. The welding rods of Examples 2 and 4-5 are significantly better than the other two welding rods in these three parameters, indicating that even if the composition is the same, changes in the material ratio may also affect the performance of the welding rod, and this effect has no specific regularity.
[0065] In addition, according to the method described in standard TB / T2375-1993, the corrosion resistance test of the weld metal obtained by welding the parent material Q345NH with the welding rods of Examples 1 to 5 was carried out. It was found that the corrosion rate of the weld metal obtained by the welding rod of Example 4 was significantly lower than that of the weld metal obtained by other welding rods and the parent material used for welding. The corrosion rate results (g / m 2 / h, corrosion for 72h, expressed as the average of 5 measurements for each sample) are as follows: the corrosion rate of the weld obtained by the welding rod of Example 1 is 3.6744±0.3043, the corrosion rate of the weld obtained by the welding rod of Example 2 is 3.0972±0.3262, the corrosion rate of the weld obtained by the welding rod of Example 3 is 4.1867±0.3547, the corrosion rate of the weld obtained by the welding rod of Example 4 is 1.5348±0.1074, the corrosion rate of the weld obtained by the welding rod of Example 5 is 3.3836±0.2649, and the corrosion rate of the parent material is 4.4257±0.4613. According to the above results, it is obvious that among all the welding rods of the present invention, although the formulations of the welding rods are similar and there is no specific regularity among the examples, it is unexpectedly found that the welding rod of Example 4 exhibits significantly excellent performance.
[0066] The present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A weathering steel welding rod, characterized in that: The invention is prepared by mixing powders in the following weight proportions uniformly, then adding potassium sodium water glass accounting for 22-27% of the total weight of the mixed powders, stirring uniformly, applying the mixture on a carbon steel welding core and drying the mixture; the weight proportions of the powders are: 20-25 parts of marble, 17-22 parts of fluorite, 2-5 parts of rutile, 3-8 parts of feldspar, 4-7 parts of lithium fluoride, 3-5 parts of ferrosilicon, 6-10 parts of electrolytic manganese, 2-4 parts of nickel powder, 1.5-3.5 parts of metal chromium, 7-10 parts of iron powder, 2-4 parts of silicon zirconium alloy, 2.5-3.5 parts of copper powder, 1.0-1.5 parts of cerium oxide, 0.5-0.8 parts of yttrium oxide, 1-3 parts of sodium alginate and 1-2 parts of soda ash.
2. The weathering steel welding rod according to claim 1, characterized in that: The specification of the welding core is Φ2.5~5.0mm; or, the specification of the welding core is Ф2.5mm, Ф3.2mm, Ф4.0mm or Ф5.0mm; or, the carbon steel welding core is H08A welding core.
3. The weathering steel welding rod according to claim 1, characterized in that: The weight ratio of the powder is (e1): 20 parts of marble, 21 parts of fluorite, 3 parts of rutile, 5 parts of feldspar, 6 parts of lithium fluoride, 3 parts of ferrosilicon, 8 parts of electrolytic manganese, 2 parts of nickel powder, 2 parts of metallic chromium, 7 parts of iron powder, 2 parts of silicon zirconium alloy, 3.5 parts of copper powder, 1 part of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 1 part of soda ash; or, The weight ratio of the powder is (e2): 22 parts of marble, 18 parts of fluorite, 2 parts of rutile, 3 parts of feldspar, 5 parts of lithium fluoride, 4 parts of ferrosilicon, 7 parts of electrolytic manganese, 3 parts of nickel powder, 1.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.4 parts of cerium oxide, 0.7 parts of yttrium oxide, 2 parts of sodium alginate, and 1.5 parts of soda ash; or, The weight ratio of the powder is (e3): 23 parts of marble, 22 parts of fluorite, 4 parts of rutile, 8 parts of feldspar, 7 parts of lithium fluoride, 5 parts of ferrosilicon, 6 parts of electrolytic manganese, 4 parts of nickel powder, 3.5 parts of metallic chromium, 8 parts of iron powder, 4 parts of silicon zirconium alloy, 2.5 parts of copper powder, 1.3 parts of cerium oxide, 0.6 parts of yttrium oxide, 2 parts of sodium alginate, and 2 parts of soda ash; or, The weight ratio of the powder is (e4): 24 parts of marble, 19 parts of fluorite, 5 parts of rutile, 7 parts of feldspar, 4 parts of lithium fluoride, 3 parts of ferrosilicon, 9 parts of electrolytic manganese, 2 parts of nickel powder, 2.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon-zirconium alloy, 3 parts of copper powder, 1.2 parts of cerium oxide, 0.5 parts of yttrium oxide, 1 part of sodium alginate, and 1.5 parts of soda ash; or, The weight ratio of the powder is (e5): 25 parts of marble, 17 parts of fluorite, 3 parts of rutile, 6 parts of feldspar, 5 parts of lithium fluoride, 5 parts of ferrosilicon, 10 parts of electrolytic manganese, 4 parts of nickel powder, 3 parts of metallic chromium, 10 parts of iron powder, 2 parts of silicon-zirconium alloy, 2.5 parts of copper powder, 1.5 parts of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 2 parts of soda ash.
4. The weathering steel welding rod according to claim 1, characterized in that: The weight ratio of the powder is (e1): 20 parts of marble, 21 parts of fluorite, 3 parts of rutile, 5 parts of feldspar, 6 parts of lithium fluoride, 3 parts of ferrosilicon, 8 parts of electrolytic manganese, 2 parts of nickel powder, 2 parts of metallic chromium, 7 parts of iron powder, 2 parts of silicon-zirconium alloy, 3.5 parts of copper powder, 1 part of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 1 part of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 27 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder of step (a), adding the mixture to the dry powder and mixing the mixture evenly, applying the mixture to a Φ4.0 mm welding core (H08A) by a hydraulic press, drying the welding rod at low temperature (45° C.) for 12 hours, and then drying the welding rod at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod; or, The weight ratio of the powder is (e2): 22 parts of marble, 18 parts of fluorite, 2 parts of rutile, 3 parts of feldspar, 5 parts of lithium fluoride, 4 parts of ferrosilicon, 7 parts of electrolytic manganese, 3 parts of nickel powder, 1.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.4 parts of cerium oxide, 0.7 parts of yttrium oxide, 2 parts of sodium alginate, and 1.5 parts of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 24 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder of step (a), adding the mixture to the dry powder and mixing the mixture evenly, applying the mixture to a Φ2.5 mm welding core (H08A) by a hydraulic press, drying the welding rod at low temperature (45° C.) for 12 hours, and then drying the welding rod at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod; or, The weight ratio of the powder is (e3): 23 parts of marble, 22 parts of fluorite, 4 parts of rutile, 8 parts of feldspar, 7 parts of lithium fluoride, 5 parts of ferrosilicon, 6 parts of electrolytic manganese, 4 parts of nickel powder, 3.5 parts of metallic chromium, 8 parts of iron powder, 4 parts of silicon-zirconium alloy, 2.5 parts of copper powder, 1.3 parts of cerium oxide, 0.6 parts of yttrium oxide, 2 parts of sodium alginate, and 2 parts of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 26 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder of step (a), adding the mixture to the dry powder and mixing the mixture evenly, applying the mixture to a Φ3.2 mm welding core (H08A) by a hydraulic press, drying the welding rod at low temperature (45° C.) for 12 hours, and then drying the welding rod at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod; or, The weight ratio of the powder is (e4): 24 parts of marble, 19 parts of fluorite, 5 parts of rutile, 7 parts of feldspar, 4 parts of lithium fluoride, 3 parts of ferrosilicon, 9 parts of electrolytic manganese, 2 parts of nickel powder, 2.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon-zirconium alloy, 3 parts of copper powder, 1.2 parts of cerium oxide, 0.5 parts of yttrium oxide, 1 part of sodium alginate, and 1.5 parts of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 23 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder of step (a), adding the mixture to the dry powder and mixing the mixture evenly, applying the mixture to a Φ4.0 mm welding core (H08A) by a hydraulic press, drying the welding rod at low temperature (45° C.) for 12 hours, and then drying the welding rod at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod; or, The weight ratio of the powder is (e5): 25 parts of marble, 17 parts of fluorite, 3 parts of rutile, 6 parts of feldspar, 5 parts of lithium fluoride, 5 parts of ferrosilicon, 10 parts of electrolytic manganese, 4 parts of nickel powder, 3 parts of metallic chromium, 10 parts of iron powder, 2 parts of silicon-zirconium alloy, 2.5 parts of copper powder, 1.5 parts of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 2 parts of soda ash; and it is prepared according to a method comprising the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 22 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ5.0 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
5. A method for preparing a weathering steel welding rod, comprising the following steps: (a) mixing the following powders in weight proportions uniformly: 20-25 parts of marble, 17-22 parts of fluorite, 2-5 parts of rutile, 3-8 parts of feldspar, 4-7 parts of lithium fluoride, 3-5 parts of ferrosilicon, 6-10 parts of electrolytic manganese, 2-4 parts of nickel powder, 1.5-3.5 parts of metallic chromium, 7-10 parts of iron powder, 2-4 parts of silicon-zirconium alloy, 2.5-3.5 parts of copper powder, 1.0-1.5 parts of cerium oxide, 0.5-0.8 parts of yttrium oxide, 1-3 parts of sodium alginate, and 1-2 parts of soda ash; (b) adding 22 to 27 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder of step (a), stirring evenly, applying the mixture to a carbon steel welding core (e.g., a H08A welding core of Φ2 to 6 mm), and then drying (e.g., drying at low temperature for 12 hours and then drying at high temperature, e.g., drying at low temperature (45°C) for 12 hours and then drying at high temperature (360°C) for 2 hours) to obtain a weathering steel welding rod.
6. The method according to claim 5, characterized in that The specification of the welding core is Φ2.5~5.0mm.
7. The method according to claim 5, characterized in that The specification of the welding core is Ф2.5mm, Ф3.2mm, Ф4.0mm or Ф5.0mm.
8. The method according to claim 5, characterized in that The weight ratio of the powder is (e1): 20 parts of marble, 21 parts of fluorite, 3 parts of rutile, 5 parts of feldspar, 6 parts of lithium fluoride, 3 parts of ferrosilicon, 8 parts of electrolytic manganese, 2 parts of nickel powder, 2 parts of metallic chromium, 7 parts of iron powder, 2 parts of silicon zirconium alloy, 3.5 parts of copper powder, 1 part of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 1 part of soda ash; or, The weight ratio of the powder is (e2): 22 parts of marble, 18 parts of fluorite, 2 parts of rutile, 3 parts of feldspar, 5 parts of lithium fluoride, 4 parts of ferrosilicon, 7 parts of electrolytic manganese, 3 parts of nickel powder, 1.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.4 parts of cerium oxide, 0.7 parts of yttrium oxide, 2 parts of sodium alginate, and 1.5 parts of soda ash; or, The weight ratio of the powder is (e3): 23 parts of marble, 22 parts of fluorite, 4 parts of rutile, 8 parts of feldspar, 7 parts of lithium fluoride, 5 parts of ferrosilicon, 6 parts of electrolytic manganese, 4 parts of nickel powder, 3.5 parts of metallic chromium, 8 parts of iron powder, 4 parts of silicon zirconium alloy, 2.5 parts of copper powder, 1.3 parts of cerium oxide, 0.6 parts of yttrium oxide, 2 parts of sodium alginate, and 2 parts of soda ash; or, The weight ratio of the powder is (e4): 24 parts of marble, 19 parts of fluorite, 5 parts of rutile, 7 parts of feldspar, 4 parts of lithium fluoride, 3 parts of ferrosilicon, 9 parts of electrolytic manganese, 2 parts of nickel powder, 2.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon-zirconium alloy, 3 parts of copper powder, 1.2 parts of cerium oxide, 0.5 parts of yttrium oxide, 1 part of sodium alginate, and 1.5 parts of soda ash; or, The weight ratio of the powder is (e5): 25 parts of marble, 17 parts of fluorite, 3 parts of rutile, 6 parts of feldspar, 5 parts of lithium fluoride, 5 parts of ferrosilicon, 10 parts of electrolytic manganese, 4 parts of nickel powder, 3 parts of metallic chromium, 10 parts of iron powder, 2 parts of silicon-zirconium alloy, 2.5 parts of copper powder, 1.5 parts of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 2 parts of soda ash.
9. The method according to claim 5, characterized in that The weight ratio of the powder is (e1): 20 parts of marble, 21 parts of fluorite, 3 parts of rutile, 5 parts of feldspar, 6 parts of lithium fluoride, 3 parts of ferrosilicon, 8 parts of electrolytic manganese, 2 parts of nickel powder, 2 parts of metallic chromium, 7 parts of iron powder, 2 parts of silicon-zirconium alloy, 3.5 parts of copper powder, 1 part of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 1 part of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 27 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder of step (a), adding the mixture to the dry powder and mixing the mixture evenly, applying the mixture to a Φ4.0 mm welding core (H08A) by a hydraulic press, drying the welding rod at low temperature (45° C.) for 12 hours, and then drying the welding rod at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod; or, The weight ratio of the powder is (e2): 22 parts of marble, 18 parts of fluorite, 2 parts of rutile, 3 parts of feldspar, 5 parts of lithium fluoride, 4 parts of ferrosilicon, 7 parts of electrolytic manganese, 3 parts of nickel powder, 1.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.4 parts of cerium oxide, 0.7 parts of yttrium oxide, 2 parts of sodium alginate, and 1.5 parts of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 24 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder of step (a), adding the mixture to the dry powder and mixing the mixture evenly, applying the mixture to a Φ2.5 mm welding core (H08A) by a hydraulic press, drying the welding rod at low temperature (45° C.) for 12 hours, and then drying the welding rod at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod; or, The weight ratio of the powder is (e3): 23 parts of marble, 22 parts of fluorite, 4 parts of rutile, 8 parts of feldspar, 7 parts of lithium fluoride, 5 parts of ferrosilicon, 6 parts of electrolytic manganese, 4 parts of nickel powder, 3.5 parts of metallic chromium, 8 parts of iron powder, 4 parts of silicon-zirconium alloy, 2.5 parts of copper powder, 1.3 parts of cerium oxide, 0.6 parts of yttrium oxide, 2 parts of sodium alginate, and 2 parts of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 26 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder of step (a), adding the mixture to the dry powder and mixing the mixture evenly, applying the mixture to a Φ3.2 mm welding core (H08A) by a hydraulic press, drying the welding rod at low temperature (45° C.) for 12 hours, and then drying the welding rod at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod; or, The weight ratio of the powder is (e5): 25 parts of marble, 17 parts of fluorite, 3 parts of rutile, 6 parts of feldspar, 5 parts of lithium fluoride, 5 parts of ferrosilicon, 10 parts of electrolytic manganese, 4 parts of nickel powder, 3 parts of metallic chromium, 10 parts of iron powder, 2 parts of silicon zirconium alloy, 2.5 parts of copper powder, 1.5 parts of cerium oxide, 0.8 parts of yttrium oxide, 3 parts of sodium alginate, and 2 parts of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 22 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ5.0 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.
10. The method according to claim 5, characterized in that The weight ratio of the powder is (e4): 24 parts of marble, 19 parts of fluorite, 5 parts of rutile, 7 parts of feldspar, 4 parts of lithium fluoride, 3 parts of ferrosilicon, 9 parts of electrolytic manganese, 2 parts of nickel powder, 2.5 parts of metallic chromium, 9 parts of iron powder, 3 parts of silicon zirconium alloy, 3 parts of copper powder, 1.2 parts of cerium oxide, 0.5 parts of yttrium oxide, 1 part of sodium alginate, and 1.5 parts of soda ash; the method comprises the following steps: (a) mixing the powders of the above materials uniformly; (b) taking 23 parts by weight of potassium sodium water glass per 100 parts by weight of the mixed powder in step (a), adding the mixed powder to the dry powder, and applying the mixed powder to a Φ4.0 mm welding core (H08A) by a hydraulic press, and drying the welding rod at low temperature (45° C.) for 12 hours, and then drying at high temperature (360° C.) for 2 hours to obtain a weathering steel welding rod.